The impact of hypothyroidism on the incidence and clinical prognosis of acute kidney injury in critically ill patients - 陈德珠; 朱满桂; 刘凌凌; 容艳辉 (Linchuang shenzangbing zazhi)
Objective To explore the relationship between hypothyroidism and acute kidney injury(AKI) in critically ill patients, and to investigate the impact of hypothyroidism on clinical prognosis of critically ill patients with AKI. Methods A total of 496 critically ill patients from internal intensive care unit of Shunde Hospital of Guangzhou University of Traditional Chinese Medicine were enrolled in this study, 28 cases were diagnosed with hypothyroidism(hypothyroidism group) and 468 cases were not coexisted with hypothyroidism(non-hypothyroidism group). The incidences of AKI for the two groups were analyzed, and the relationship between hypothyroidism and AKI in critically ill patients were explored by logistic regression analysis. We summarized the clinical data of patients with AKI to analyze the impact of hypothyroidism on the clinical prognosis, in the aspects including mortality rate, proportion of continuous renal replacement therapy and intensive care unit stay duration in this study. Results The incidence of AKI in critically ill patients with hypothyroidism was higher than that in critically ill patients without hypothyroidism(57.1% vs 29.9%, χ~2=9.085, P=0.003), and most of AKI cases were AKI stage 2 and 3. The mortality during hospitalization(56.3% vs 31.4%, P=0.047)and intensive care unit stay duration [10(7,13)day vs 7(4,9)day, P=0.035]in critically ill AKI patients with hypothyroidism were higher than those without hypothyroidism, with the difference of statistical significance. However, there was no statistical differences in the proportion of continuous renal replacement therapy between the two groups(31.3% vs 21.4%, P=0.372). Multivariate logistic regression analysis showed that hypothyroidism(OR:1.478, 95%CI: 1.217～1.579, P=0.027), higher APACHE II score(OR:1.898, 95%CI: 1.765～2.089, P=0.008), medical history of nephrotoxic antibiotics(OR:1.428, 95%CI: 1.312～1.521,P=0.042) and sepsis(OR: 2.283, 95%CI: 2.197～2.489, P=0.035) were independent risk factors for AKI in critically ill patients. Conclusions Hypothyroidism may increase the risk for AKI in critically ill patients, also increase mortality and longer intensive care unit stay duration of the patients, affect clinical prognosis of critically ill patients, and should be concerned fully.